Movement, breakdown and persistence of carbofuran in rice field microcosm - Mohamad, Rosli; Arshad, Juzu Hayati; A. Rahman, Ismail (1990)

(untitled)
Movement, breakdown and persistence of 14C-carbofuran in a rice field simulation, comprising soil, water, rice plants and fish in a tank, were studied in Malaysia. The level of carbofuran in the water declined rapidly; about 80% of the total carbofuran applied was lost within 14 days after application (DAA). Correspondingly, an increase representing about 70% of the total applied was recorded in soil within 21 DAA, with higher levels appearing in the upper 5 cm layer and lesser amounts in the lower layers. Most of the residues remained bound to soil particles. Bound residues in the soil increased with time but extractable residues decreased. The build-up of carbofuran residues in the plants was slow and reached a maximum level, representing 28% of the total applied, at 28 days after transplanting, when accumulation of residues occurred in the aerial parts of the plants. After 7 DAA, accumulation was more pronounced in the root region. In dehusked rice grain, some residues were detected only at 90 DAA. All the fish died within 24 h of carbofuran application. Toxic metabolites of 3-keto and/or 3-hydroxy carbofuran were detectable in the water. Only carbofuran phenol and 3-hydroxy carbofuran were found in the soil and rice plant, respectively